2000
DOI: 10.1023/a:1011071907047
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ability of the naturally occurring ether lipid, 1-O (2 methoxy) hexadecyl glycerol (MHG), and phenylbutyrate (BP) to inhibit cellular proliferation, anchorage-independent growth and cellular invasion in the human prostate cancer LnCap and DU145 cells was determined. Both MHG and PB inhibited the malignant properties of these prostate cancer cells. The concentrations required to achieve similar inhibitory effect, however, were significantly different for these two agents. MHG inhibited cell growth with equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Ectopic expression of the PAF receptor in normal rat kidney mesenchymal fibroblasts, however, has been reported to suppress v-src-or v-ras-induced transformation (Kume and Shimizu, 1997). We had earlier shown that 1-O(2-methoxy) hexadecyl glycerol, a lipid with similar aliphatic fatty acid chains to that of PAF is biologically active and suppresses the malignant properties of human colon and prostate cancer cells (Wang et al, 1999;Reynolds et al, 2000). In this study, we showed that PAF-activated MAP kinases, induced a more differentiated phenotype and suppressed the malignant properties of human colon carcinoma cells.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Ectopic expression of the PAF receptor in normal rat kidney mesenchymal fibroblasts, however, has been reported to suppress v-src-or v-ras-induced transformation (Kume and Shimizu, 1997). We had earlier shown that 1-O(2-methoxy) hexadecyl glycerol, a lipid with similar aliphatic fatty acid chains to that of PAF is biologically active and suppresses the malignant properties of human colon and prostate cancer cells (Wang et al, 1999;Reynolds et al, 2000). In this study, we showed that PAF-activated MAP kinases, induced a more differentiated phenotype and suppressed the malignant properties of human colon carcinoma cells.…”
mentioning
confidence: 53%
“…(Figure 1b). Since the induction of Waf1/p21 is associated with growth inhibition and the induction of differentiation (Di Cunto et al, 1998;Chakrabarty et al, 1998), we determined the effect of PAF on CEA production, a differentiationrelated marker for colon carcinomas (Chakrabarty et al, 1988;Guadagni et al, 1990;Reynolds et al, 1998Reynolds et al, , 2000Wang et al, 1999). A one-time treatment of these cells (healthy and actively proliferating) with PAF (5-10 mm) induced a significant increase in CEA production Figure 2 Effect of PAF on anchorage-independent growth and cellular invasion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both human prostate cancer LnCap and DU145 cell lines have responded to the antiproliferative effect of MHG in a similar manner [48]. …”
Section: Discussionmentioning
confidence: 99%
“…[48] observed that both the human prostate cancer LnCap and DU145 cell lines responded to the antiproliferative effect of MHG in a similar manner. In this study MHG inhibited cell growth with equal potency in these cell lines with an IC-50 value of 93 μM for LnCap, and 97 μM for DU145 while the IC-50 values for phenylbutyrate were 1.3 mM and 7.3 mM, respectively, for LnCap and DU145 cells.…”
Section: Alkylglycerols Studiesmentioning
confidence: 99%